Potassium, magnesium and pyridoxine in the context of the biological effects of estrogens - O A Gromova; I Yu Torshin; I K Tomilova; L K Dzhidzhikhiya; N V Kerimkulova (IP Berlin A.V., 2017)
Potassium and magnesium ions are essential for realizing the biological effects of estrogens. Magnesium ions promote the translocation of the estrogen receptors into the nucleus of the cell and regulate the potassium channels that are involved in the regulation of arterial pressure by means of estrogens. In the central nervous system, potassium and magnesium ions interact with the neurosteroids of estrogens and various neurotransmitters (g-aminobutyric acid, epinephrine, opioids, acetylcholine). Vitamin B6 (pyridoxine) increases the bioavailability of magnesium and is a pharmacodynamic synergistic of magnesium and potassium. Therefore, hormone replacement therapy with estrogens (which contributes in part to the formation of magnesium and pyridoxine deficiencies) should be accompanied by an adequate combination of potassium, magnesium and pyridoxine.